The Producing Of Environmental Friendly Geopolymer Cement With Raw Material Of Basalt Minerals To Accomplish Welfare Lampung - Muhammad; Suharto (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
Cement was an important building material for a development and the need for cement sharply increased along with the development of people structures and infrastructures. Together with the increase of demands on cement went increase the level of environment pollution due to the process of cement indutries because the process released carbon dioxide (CO2) gas to the atmosphere. Geopolymer cement was an alternative to replace the unenvironmental-friendly cement with synthetizing materials riched in silicate-aluminate in form of basalt minerals. Based on XRF analysis, basalt minerals were a pozolan meterial due to their high silica and alumina contents which were 56.15 % SiO2, 17.37 % Al2O3, 8.25 % CaO and 4.62 % Fe2O3. Basal minerals were synthetized to geopolymer in the activator NaOH solution varied to 2.5, 3.9, 6 and 8 % with the addition of 9.75 % sodium silicate thence were cured at the temperatures of 60, 80, dan 100 oC for 5 hours. The charactization of basalt-minerals geopolymer cement indicated the optimum pressurestrength on the addition of 3.9 % NaOH to 435 kg/cm2at the temperature of 60 oC, 589 kg/cm2at 80oC, dan 598 kg/cm2at 100oC. Porosity value decreased with the addition oh NaOH and curing temperature with the optimum porosity value with the addition of 3.9 % NaOH to achieve 9.82 % at 60 oC, 9.46 % at 80 oC, and 7.30 % at 100 oC. With addition of 6 %NaOH, the porosity increased back to 13.10 % at 60 oC, 12.08 % at 80 oC, and 10.18 at 100 oC. On the quality of pressurestrength, basalt-minerals geopolymer cement held high as compared with the standard of conventional cementwhich were 324 kg/cm2and the porosity of 21.28 %. Basalt minerals could be utilized as raw material to produce geopolymer cement due to the better quality of the cement than the conventional cement and feasible to develop as environmental-friendly cement.